2020
DOI: 10.1016/j.heliyon.2020.e03575
|View full text |Cite
|
Sign up to set email alerts
|

Influential variables in the Journal Impact Factor of Dentistry journals

Abstract: The aim of this contribution is to determine what variables influence the position, by quartiles of the impact factor, as a quality indicator of a journal in the field of Dentistry. Methods: To this end, 24 journals included in Journal Citation Reports, 6 pertaining to each quartile were selected by a stratified sampling and then an ordinal regression model was estimated stepwise considering the journal impact factor quartile as response variable. Results: The estimation procedure concluded that the average nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies have reported many recommendations to improve the journal impact factor. [18][19][20] These recommendations, valid for all journals, may allow the Journal of Craniofacial Surgery journal to increase its impact factor in the long run. In this context, it is beneficial to publish accepted articles as "published ahead-of-print" in a short time, to send invitations to leading academicians for systemic reviews, and to improve the visibility and accessibility of published articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported many recommendations to improve the journal impact factor. [18][19][20] These recommendations, valid for all journals, may allow the Journal of Craniofacial Surgery journal to increase its impact factor in the long run. In this context, it is beneficial to publish accepted articles as "published ahead-of-print" in a short time, to send invitations to leading academicians for systemic reviews, and to improve the visibility and accessibility of published articles.…”
Section: Discussionmentioning
confidence: 99%
“…Although journal impact factors can be manipulated, the ideal is to increase journal impact factors through ethical means by excluding manipulation. Previous studies have reported many recommendations to improve the journal impact factor 18–20 . These recommendations, valid for all journals, may allow the Journal of Craniofacial Surgery journal to increase its impact factor in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Valderrama et al. 13 found that both the average number of manuscripts and the percentage of systematic reviews have the most influence on the Journal Citation reports and a significant influence on the Journal Impact Factor.…”
Section: Discussionmentioning
confidence: 99%